Egg yolk powder an alternative to fresh-egg yolk for buffalo semen cryopreservation - SINGH, MAHAK; BARIK, NIRMAL CHANDRA; GHOSH, S K; PRASAD, J K; RAJORIA, J S; SONI, Y K; KUMAR, ASHOK; CHAUDHARY, J K; SRIVASTAVA, N (The Indian Journal of Animal Sciences, 2015)
The present work was carried out to evaluate the effect of commercial egg yolk (EY) powder as an alternative to fresh EY on buffalo semen freezability. Ejaculates (12) from 3 bulls (4 from each bull) were collected as per standard procedure. After initial selection of ejaculates on the basis of mass activity (+3 and above) and individual progressive motility (70% and above), ejaculates were divided into 3 parts and diluted with tris dilutor, G1, containing 5% EY powder; G2, containing 10% EY powder, and G3, containing fresh EY (20%). Ejaculates were processed and cryopreserved using automated biological cell freezer followed by examination of frozen samples after 24 h. Semen quality variables (individual progressive motility, viability using propidium iodide, acrosome integrity using FITC-PSA and membrane integrity by HOST) were examined at fresh and post-thaw stage. At fresh stage semen quality variables did not vary among 3 groups.